Effect of intermittent drying and storage on parchment coffee quality - Borém, Flávio Meira; Isquierdo, Eder Pedroza; Oliveira, Pedro Damasceno [UNESP]; Ribeiro, Fabiana Carmanini; Siqueira, Valdiney Cambuy; Taveira, José Henrique da Silva (My University, 2014)
This work aimed to evaluate the effects of intermittent drying on the quality of the coffee, after twelve months of storage. The parchment coffee was submitted to two days of pre-drying on the ground, and soon afterwards, mechanically dried until reaching a moisture of 16%, 20% and 24% (wb); later, the coffee remained under tempering for two, six and twelve days in wooden boxes. After each tempering period, the drying was completed until the coffee reached a moisture of 11% (wb). The control consisted of continuous drying up to 11% (wb). After the drying until an 11% (wb) moisture, the coffee was stored for twelve months. After that period electric conductivity, potassium leaching, total reducing and non-reducing sugars, total titratable acidity analyses and sensorial analysis of the coffee were conducted. The values of electric conductivity indicated that the coffees submitted to two and six days of tempering until the restart of the drying, independent of the moisture when the drying was interrupted, presented lower degradation levels of the cellular membrane system, when compared with the coffees submitted to the continuous and intermittent drying, with twelve days of tempering until the resumption of drying. It was verified that, for the other analysis there was no significant difference among the treatments.
Efeito da secagem intermitente e do armazenamento na qualidade do café em pergaminho
Keywords: Chemical analysis; Coffea arabica L; Moisture content; Sensorial analysis; Tempering time